THE EFFECT OF PUBLICITY OF THE PRESIDENT DIRECTOR AND MAJORITY SHAREHOLDERS ON TAX AVOIDANCE - Ivastya, Raras; Fanani, Zaenal (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2020)
The study uses the volume search index (SVI) to see the publicity of the president director through Google Trends, and uses the percentage of share ownership to see stocks that aim to influence tax avoidance. The research object used is a public company registered at PT. Indonesia Stock Exchange and the 50 richest people listed on Forbes in the 2013-2018 period. The sample data of selected companies were 24 companies of 121 observation data for 6 years. This study uses multiple linear analysis. The results of the study support the first hypothesis which indicates that the main director who gets higher attention will do tax avoidance. Firms with higher publicity tend to use more tax planning services from auditors. While the research results contradict the second hypothesis that the higher the share owner will not do tax avoidance.In the end, it is hoped that the results of this research can be used to encourage the government to accelerate the Base Erosion and Profit Shifting mechanism which can be used as a reference for investors and company management to improve tax avoidance strategies so that in the future it will provide maximum benefits for the firm sustainability.